(untitled) (Journal of the College of Basic Education, 2023)
Mass attenuation coefficient values for Swedish board wood ( ρ = 0.5065.g.cm-3 ) at gamma energies 186.2, 242, 295.2, 351.9, 609.3, 768.3, 1120.3, 1238.1 and 1764.5 KeV were measured by using HPGe detector, the radiation source used in the experiment was . These coefficients were also calculated by XCOM code. The experimental result obtained gives good agreement with calculated values and the mass attenuation coefficient for Swedish board wood obtained in this research was decreased with increasing photon energy.